2015
DOI: 10.1002/pola.27690
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)(tpy)2-functionalized hydrogels: Synthesis, reversible responsiveness, and coupling with the belousov-zhabotinsky reaction

Abstract: This work aims at developing an approach to Ru(II)(Tpy) 2 -functionalized hydrogels and exploring the coupling of the hydrogels with the Belousov-Zhabotinsky (BZ) reaction. Based on free radical polymerization, two synthetic routes are developed. The first one is the direct gelation by copolymerization of acrylamide as hydrophilic component and Ru(II)(Tpy) 2 as the functional group. The second one is carried out through a combined approach. A terpyridine-containing hydrogel is first prepared and then post-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[24] Two synthetic routes were developed to prepare Ru(II)(Tpy) 2 -functionalized polymer hydrogels. The first one is the direct gelation by copolymerization of acrylamide (as a hydrophilic component) and Ru(II)(Tpy) 2 (as the functional group).…”
Section: Covalently Crosslinked Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[24] Two synthetic routes were developed to prepare Ru(II)(Tpy) 2 -functionalized polymer hydrogels. The first one is the direct gelation by copolymerization of acrylamide (as a hydrophilic component) and Ru(II)(Tpy) 2 (as the functional group).…”
Section: Covalently Crosslinked Hydrogelsmentioning
confidence: 99%
“…Different from metallocene‐containing hydrogels, Zhou et al reported Ru(II)(Tpy) 2 ‐functionalized polymer hydrogels with metal centers linked by coordination interactions . Two synthetic routes were developed to prepare Ru(II)(Tpy) 2 ‐functionalized polymer hydrogels.…”
Section: Covalently Crosslinked Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example, Yu and co-workers demonstrated that the architecture of the conductive polymer phase played an important part in determining the conductivity of hybrid ECHs. Although high conductivity (0.8 S/m) was obtained, the stretchability of the hydrogels is limited by the N , N ′-methylenebisacrylamide (BIS)-cross-linked network structures, which are often fragile and cannot withstand large deformations in stretchable electronics. …”
Section: Introductionmentioning
confidence: 99%
“…This may be another reason why the DC hydrogels are highly stretchable and tough. Transmission electron microscope (TEM) analysis of the fracture surface of freeze‐dried DC hydrogel revealed a completely different morphology compared with traditional hydrogels cross‐linked by BIS (Figure S1, Supporting Information) . The fracture surface of DC hydrogel does not have porous structures and exhibits tightly cross‐linked structure.…”
Section: Resultsmentioning
confidence: 99%